Anesthesia for Pars Plana Vitrectomy with Insulin Needle, Is It Possible? - Waleed Riad; Nauman Ahmed; Emad Abboud; Essam Al-Harthi; Eman Kahtani (Anesthesiology Research and Practice)
Peribulbar block is commonly used for ocular posterior segment surgery. This work aimed to compare the efficacy of using 12.5 mm to 25 mm standard needle length in performing single injection peribulbar block for retinal surgery. Peribulbar block was performed in 120 patients using either standard 25 mm or 12.5 mm 30 G needle (insulin needle). While applying digital pressure around the needle hub, 8–10 mL of local anesthetic are injected. Ocular movement was assessed at 5 and 10 min using simple akinesia score (0–8). If after 10 min score was >1, supplementary injection was given. Visual analogue scale (0–10) was used at the end of the procedure to assess surgeons’ satisfaction and patients’ intraoperative pain. No differences in akinesia score at 5 & 10 min (P=0.34 and 0.36, resp.). Initial volume injected was comparable between groups (P=0.31), however total volume of local anesthesia and supplementary injections were significantly higher in 12.5 mm group (P=0.03 and 0.01, resp.). No difference as regard surgeons’ satisfaction and patients’ intraoperative pain (P=1.0 and 0.18, resp.). Peribulbar block with 12.5 mm needle together with digital compression is a suitable alternative to the standard block with 25 mm needle length for retinal surgery.